INNOVATIVE APPROACHES TO THE PRODUCTION OF COMPOUND FEED ON THE FARM - Piskun, Viktor; Yatsenko, Yury; Antonenko, Serhii; Zolotarov Andrіі; Zolotarоva Svitlana (SWorld-Ger Conference proceedings, 2024)
Purpose. To develop and test the technology of compound feed production in production conditions to determine the main technical and economic indicators.Results. On the basis of the patent for utility model 38620 Ukraine, the technology for the produc